Concerted Quantification: How Knowledge Workers Limit Overwork While Maintaining Client Satisfaction - Conzon, Vanessa M.; Mellody, James C. (Organization Science, 2025)
Knowledge workers are increasingly overworked, with negative consequences for both individuals and organizations. Pressures for long hours often come from clients, and the quantification of work has, in many cases, amplified these pressures. We examine when and how workers might rely upon quantification to limit overwork. We draw on data from a 21-month ethnography of information technology worker teams that develop software for clients in finance. We find that although these workers faced overwork pressures, they managed this tension through a process we label “concerted quantification.” This process has three steps. First, team members constructed quantified units based on disparate work tasks to coordinate on a specific set of tasks that would likely limit overwork. Second, workers leveraged these quantified units to create flexibility in when specific work tasks were performed, allowing workers to limit overwork when facing fluctuating work demands. Third, workers promoted quantified units to clients as a standard measure of performance, establishing the completion of these units as a key criterion for work success. Particular substantiations of common characteristics of knowledge work—team autonomy, task expertise, and shared quality norms—are conditions for concerted quantification. Overall, we find that quantifying processes (a) help teams determine an appropriate amount of work to take on without engaging in overwork and (b) set clients’ expectations for the amount of work to be completed. We contribute to research on overwork and quantification by highlighting how quantification can, under certain conditions, support workers in limiting overwork.